Pelayanan Publik dalam Kepemimpinan Profetik oleh Umar Bin Khattab - Amrin Sofian; Asmal May; Zamsiswaya Zamsiswaya (UIN SUSKA RIAU, 2022)
Leadership has a direct influence on the final outcome of a government, especially in serving its people. Umar bin Khattab's leadership pattern certainly brings educational values. So This study examines the influence of educational values in Umar Bin Khattab's prophetic leadership on public services in Indonesia in the current era. This research is literature research and the methodology used in this research is character study. The data related to this study were collected through literature study and presented with descriptive analysis techniques, namely by explaining the policies of Umar bin Khattab in public services, by referring to the book of Umar bin Khattab historia as primary data and related literature books as data. secondary. The results of this study are the educational value of Umar Bin Khattab's leadership on public services, namely the bookkeeping of the Qur'an, qira'at education, Tafsir bil Ra'yi education, education in the dissemination of hadith and infrastructure education (architect). Then regarding the influence of Umar Bin Khattab's prophetic leadership on public services in Indonesia, namely the role of I'tiqadiyah, controlling the salary and land tax payment system, establishing a state court by dividing it into the judicial, legislative and executive systems, and establishing a security system, as the center of the police and military. And the last influence is the Islamic calendar, which makes it easy to determine worship for all Muslims. Keywords: Public Service, Prophetic, Umar bin Khattab.